The Preference of Alevis according to The Results of The Referendum on 16th April 2017 (The Example of Sivas Province) (Journal of Alevism-Bektashism Studies, 2018)
Voters are influenced by various factors while voting and accordingly they make their choices and act by voting. Since 1980’s, all over the world politics has been increasingly determined by cultural identities. In our country also, as party affiliations started widely to be defined by cultural identities, the relationship between ethnic and religious backgrounds and politics has become one of the important factors which determine voters’ behavior. Similar choices are made during the referendum, too. Voters usually vote in referendum in line with the view defended by the party they support. Alevis who played a critical role in the elections throughout Turkish political history, generally use their votes in favor of the Republican People’s Party. In this way Alevis cease to be an alternative for nationalist and sectarian right-wing parties, from which they stay away all along, and they became the grassroots of the Republican People’s Party. This paper aims to ascertain the factors affected the Alevi voters who predominantly used “No” vote in the referendum on 16 April. Within this scope, the referendum election results from the Sivas Province were analyzed.